The Influence of Positive Thinking Therapy For Anxiety on Students - Aisyah Bahiyyah; Anis Marceleni; Jhoni Wijaya (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This study investigated the impact of positive thinking therapy on anxiety levels in third semester psychology students. Using a One Group Pretest-Posttest design, which involved 20 participants with (17 female, 3 male). In the normality test results, the significance value of the pretest is included in the normal distribution with a Sig value = 0.365 (p> 0.05) as well as the significance value of the posttest is included in the normal distribution with a Sig value = 0.371 (p> 0.05). in the pretest the significance value is 0.583 (≥0.05) and in the posttest the significance value is 0.560 (≥0.05) thus in the initial test (pretest) and the final test (posttest) both have homogeneous data. Finally, in the Hypothesis test using the Paired Sample T-test, the Significance value of the pretest and posttest is <0.001 so that H1 is accepted, thus the researcher can conclude that the therapy succeeded in reducing anxiety levels for most participants, only three did not experience changes. Statistical analysis supports this conclusion, showing the effectiveness of therapy in reducing anxiety.